Request speech act in Malaysian Chinese Mandarin - Pang, Ming; Abdul Halim, Hazlina; Mohd Jalis, Farhana Muslim; Lu, Chuanhao (Tarbiat Modares University, 2024)
Request is used quite often in Malaysian Chinese people’s daily life. Most previous researchers focused on request speech act in mainland Chinese language. However, very little attention is paid to the request speech act in Malaysian Chinese. This study aims to investigate the request speech act in Malaysian Chinese Mandarin. Role play method was employed to elicit data needed for this study. 25 Malaysian Chinese participants and 1 Malaysian Chinese interlocutor were recruited to role play 12 scenarios. The collected data underwent analysis using a revised framework for coding. The results unveiled that the most commonly utilized strategy was conventionally indirect strategy, followed by direct strategy. The least frequently used one was non-conventionally indirect strategy. More external modifiers were used than internal modifiers. Variables of social distance, and ranking of imposition had impacts on request speech act in Malaysian Chinese Mandarin. Social power did not influence the use of ‘query preparatory’ and ‘want statements’ strategy. This study can be of great value with regard to theory and practice. Theoretically, it revises and validates the CCSARP theoretical framework with Malaysian Chinese Mandarin data. Practically, it can improve communication skills in Malaysian Chinese people’s everyday interactions and help them maintain positive relationships.